Transport in Caco-2 Cell Monolayers of Antidiabetic Cucurbitane Triterpenoids from Momordica charantia Fruits - Wu, Shi-Biao; Yue, Grace G. L.; To, Ming-Ho; Keller, Amy C.; Lau, Clara B. S.; Kennelly, Edward J. (Planta Medica, 2014)
Bitter melon, the fruit of Momordica charantia L. (Cucurbitaceae), is a widely-used treatment for diabetes in traditional medicine systems throughout the world. Various compounds have been shown to be responsible for this reputed activity, and, in particular, cucurbitane triterpenoids are thought to play a significant role. The objective of this study was to investigate the gastrointestinal transport of a triterpenoid-enriched n-butanol extract of M. charantia using a two-compartment transwell human intestinal epithelial cell Caco-2 monolayer system, simulating the intestinal barrier. Eleven triterpenoids in this extract were transported from the apical to basolateral direction across Caco-2 cell monolayers, and were identified or tentatively identified by HPLC-TOF-MS. Cucurbitane triterpenoids permeated to the basolateral side with apparent permeability coefficient (Papp) values for 3-β-7-β,25-trihydroxycucurbita-5,23(E)-dien-19-al and momordicines I and II at 9.02 × 10−6, 8.12 × 10−6, and 1.68 × 10−6 cm/s, respectively. Also, small amounts of these triterpenoids were absorbed inside the Caco-2 cells. This is the first report of the transport of the reputed antidiabetic cucurbitane triterpenoids in human intestinal epithelial cell monolayers. Our findings, therefore, further support the hypothesis that cucurbitane triterpenoids from bitter melon may explain, at least in part, the antidiabetic activity of this plant in vivo.
Keywords: Momordica charantia; Cucurbitaceae; bitter melon; cucurbitane triterpenoid; Caco-2 cells; diabetes treatments